Synthesis and Antibacterial Activity Studies of Some 2-(Substitutedphenyl)-3-bis2, 4-(4′-methylphenylamino)-s-triazine-6-ylaminobenzoylamino-5-H-4-thiazolidinone - Mukesh Kumar Ahirwar; S. P. Shrivastava (E-Journal of Chemistry)
Some 4-thiazolidinone derivatives 6(a-l) have been prepared bearing s-triazine moiety by the condensation of Schiff bases from bis-2,4 (4′-methyl-phenylamino)-s-triazine-6-ylaminobenzoyl substituted benzylhydrazone 5(a-l) with thioglycolic acid. The structures of synthesized compound have been characterized by IR, 1HNMR spectral studies. The synthesized compounds 6(a-l) has been screened for antibacterial activity.